Maxwell Electrodynamics Subjected to Quantum Vacuum Fluctuations - Gevorkyan, Ashot S.; Gevorkyan, Araksya A. (Mathematical Problems of Computer Science, 2021)
The propagation of electromagnetic waves in vacuum is considered taking into account quantum fluctuations in the limits of Maxwell-Langevin (ML) equations. For a model of "white noise" fluctuations, using ML equations, the second order partial differential equation is found which describes the quantum distribution of virtual photons in vacuum. It is proved that in order to satisfy observed facts, the Lamb Shift etc, the virtual photons should be quantized in nonperturbed vacuum. For a model of the reverse harmonic quantum oscillator, the quantum distribution of photons is obtained precisely. It is shown, that the quantized virtual photons having negative energies, in toto (approximately 85 percent) are condensed on the energy level absolute value of which is minimal. It is proved that the extension of Maxwell electrodynamics with inclusion of vacuum quantum field fluctuations may be constructed on 6D space-time continuum with 2D compactified subspace. The problem of propagation of various types electromagnetic waves in vacuum is investigated. Their influence on the refraction index of vacuum is studied.